The Radio Fundamental Catalog. I. Astrometry - L. Y. Petrov; Y. Y. Kovalev (The Astrophysical Journal Supplement Series)
We present an all-sky catalog of absolute positions and estimates of correlated flux density of 21,942 compact radio sources determined from processing interferometric visibility data of virtually all very long baseline interferometry (VLBI) observing sessions at 2–23 GHz from 72 programs suitable for absolute astrometry collected for 30 yr. We used a novel technique of generation of a data set of fused observables that allowed us to incorporate all available data in our analysis. The catalog is the most complete and most precise to date. It forms the foundation and reference for positional astronomy, space geodesy, space navigation, and population analysis of active galactic nuclei (AGNs), and provides calibrators for phase referencing for differential astrometry and VLBI astrophysical observations. Its accuracy was evaluated through a detailed accounting of systematic errors, rigorous decimation tests, comparison of different data sets, and comparison with other catalogs. The catalog preferentially samples AGNs with strong contemporary parsec-scale synchrotron emission. Its milliarcsecond-level positional accuracy allows association of these AGNs with detections in a wide range of the electromagnetic spectrum from low-frequency radio to γ rays and high-energy neutrinos. We describe the innovative data processing and calibration technique in full detail, report the in depth analysis of random and systematic positional errors, and provide a list of associations with large surveys at different wavelengths.